European citizenship: with a nation-state, federal, or cosmopolitan twist? - Olsen, Espen D.H. (Oslo, 2011)
"European citizenship poses a theoretical challenge to the paradigmatic understanding of citizenship as congruence between nation, state, and membership rights. This challenge is addressed in this paper by focusing on ideal typical models of the EU polity. Is EU citizenship more nation-based, federal, or cosmopolitan?"